Assessment of clinical cases using ABO discrepancy index - Pyakurel, Ujjwal; Thapaliya, Kamal Babu; Gupta, Sujaya; Gupta, Alka; Dhakal, Jyoti (Orthodontic Journal of Nepal, 2018)
Introduction: The American Board of Orthodontics objectively quantifies the complexity of malocclusion before orthodontic treatment. This study aims to assess the complexity of cases as measured by ABO discrepancy index (DI) in the patients under treatment by the orthodontics residents of Kantipur Dental College (KDC). Additional objectives were to 1) Ascertain DI relative to sex, age and race/ethnicity, and 2) Differential analysis of the components of the DI. Materials & Method: DI was determined for 220 consecutive cases started by orthodontic residents of KDC in a three-year graduate orthodontics program from 2014-2018. The DI was scored and compared with the patient’s sex and age. Result: The DI is not statistically significant to age, sex and race/ ethnicity. The mean DI score (± SD) was 18.65 (±10.521). Differential analysis of the components of the DI showed that the highest scores were for cephalometric measures, followed by overjet, crowding, occlusion, and the lowest scores were for lingual posterior crossbite. Conclusion: The DI was a relatively reliable index for measuring malocclusion severity. It is independent of patient’s age and race/ethnicity but is dependent on sex. Area of possible future improvements includes malocclusion sub-categories (Class II div. 1 and 2), and scores for bony and soft tissue impactions.